Convergence in action: A case study of the Norwegian internet - Hanne Kristine Hallingby; Gjermund Hartviksen; Silvia Elaluf-Calderwood; Carsten Sørensen (International Telecommunications Society (ITS), 2012)
The conceptual framework for understanding the logical Internet is based on the construction of a horizontal, layered architecture, which differentiates between physical-, data link-, network-, transport-, and application layers (1). This is different from the telecommunication networks model where a new service traditionally used to require a new network architecture to be established (2). However, the digitalization of services and products offered over the telecom infrastructure allows us to observe an emergent phenomenon of increased vertical integration on the Internet as well as the creation of further service specialization opportunities for telecom operators and users (3). We propose in this paper that this development and change in the way services are provided, leads to a new type of Internet - an addition to the current best effort Internet. This paper presents the case study of the Internet in Norway, analysing 166 of the approximately 40.000 independent AS numbers registered worldwide as catering for end-to-end services. The paper categorizes the Norwegian AS numbers according to size and type of services. Through our analyses two major groups of actors can be identified, each of them seeking to gain strategic advantage from the current Internet traffic growth: 1) Content providers and hosts seek to have a highly reliable network access with a minimal set of traffic or transmission costs. One action is to acquire AS numbers and use settlement-free peering agreements for distribution of their traffic, which is possible in traffic exchange regimes rooted in symmetry, slowly becoming asymmetric; 2) Internet access providers (IAPs) seek to take control over incoming traffic growth by hosting content within their own network and thereby to rebalance traffic and create new revenue streams with content hosting and premium end-to-end connection on-net. Our findings support the hypothesis that Internet is becoming both more vertically integrated and converged, and more specialized or modularized (4).
Keywords: 330; convergence; modularity; Internet; Internet outsourcing; Norway; autonomous systems